STRATEGIES FOR ANESTHESIA MANAGEMENT OF CESAREAN DELIVERIES WITH ABNORMAL PLACENTAL PLACEMENT–ANESTHETIST’S PERSPECTIVE - Ahmad, Maqsood (Pakistan Armed Forces Medical Journal, 2021)
Objective: To discuss problems faced in the management of emergency and elective cesarean sections with known or unknown abnormal placental placement and their management.Study Design: Retrospective observational study.Place and Duration of Study: Different Hospitals for the last 7 years from 2013 to 2020.Methodology: This retrospective observational study of 120 cases was selected for data collections that underwent anesthesia. Variables under study were age, weight, type of abnormal placenta, fluid, blood/blood products given during surgery, hysterectomy done, general surgeon help required, anesthesia type, and redo of operations.Results: A total of 120 patients were operated having abnormal placentation. The frequency of placenta previa 90 (75%), and accreta was 30 (25%). Primigravida patients were 19 (15.8%) and multigravida patients were 101 (84.1%). hysterectomy was done in 28 (23.3%) patients. Spinal anesthesia was given in 50 (41%) patients while 70 (58.3%) patients have general anesthesia. The spinal anesthesia was later on converted to general anesthesia in 32 (26.6%) patients out of 50 (41%). Only 12 (10%) patients were reopened for uncontrolled bleeding and 4 (3.3%) patients were sent to tertiary care hospital for further management. The general surgeon was called for help in 24 (20%) of patients and bladder injury occurred in 25 (20.8%) patients. No mortality was found during this period.Conclusion: Abnormal placental placement is a threat to mother life as well fetus and team of dedicated doctor is required to deal with this emergency. Use of inotropes can help to save the precious lives.